2020
DOI: 10.1002/prp2.653
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological hypothesis: TPC2 antagonist tetrandrine as a potential therapeutic agent for COVID‐19

Abstract: We wish to draw attention to the possibility of repurposing the existing calcium channel blocking drug tetrandrine for the treatment of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Tetrandrine is a bisbenzylisoquinoline that can be extracted from the perennial vine plant Stephania tetrandra S Moore (Chinese patent WO2004009106A1, 2002), which has been used in traditional Chinese medicine (TCM) (1-3, and references therein). It can also be synthesized chemically (US Patent 10,023,584 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 70 publications
0
28
0
Order By: Relevance
“…According to Riva et al, hanfangchin A , also called tetrandrine (TET) ( Figure 6 ), showed dose-dependent antiviral activities [ 82 , 83 ]. TET is a benzyltetrahydroisoquinoline alkaloid isolated from the root of the plant Stephania tetrandra with several pharmacological effects [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to Riva et al, hanfangchin A , also called tetrandrine (TET) ( Figure 6 ), showed dose-dependent antiviral activities [ 82 , 83 ]. TET is a benzyltetrahydroisoquinoline alkaloid isolated from the root of the plant Stephania tetrandra with several pharmacological effects [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was hypothesized that TET could work by blocking the two-pore channel 2 (TPC2) located in the membranes of host endolysosomal compartments by which SARS-CoV-2 can egress from these organelles and continue its replication [ 83 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations